Type 1 diabetes, periodontal health, and a familial history of hyperlipidaemia is associated with oral microbiota in children: a cross-sectional study - Caitlin A. Selway; Emilija D. Jensen; Alexia S. Pena; Gabrielle Smart; Laura S. Weyrich (BMC, 2023)
Abstract Background Hyperlipidaemia may play a significant role in the interrelationship between type 1 diabetes (T1D) and periodontal disease. A potential mechanism that links these three aspects together is the oral microbiota. We wanted to determine if there is an association between hyperlipidaemia, periodontal disease, and the oral microbiota of children with T1D, as this has not yet been explored. Methods In a post-hoc, cross-sectional study using 16S rRNA gene sequencing, we explored links between oral bacterial diversity and composition of gingival swab samples from 72 children with T1D to periodontal risk factors and hyperlipidaemia status of first-degree relatives. While multiple periodontal risk factors were assessed, we used periodontal pocket depth of 3 mm to characterise periodontal risk. As periodontal pocket depth confounded the analysis of familial history of hyperlipidaemia, a multivariate analyses were performed (i.e., no periodontal risk markers in children with or without a family history of hyperlipidaemia were compared to counterparts who did not have periodontal risk markers) to examine linkages between these factors and diversity and composition of the microbiome. Results In participants with no periodontitis risk, children with a family history of dyslipidemia had different bacterial diversity and composition compared to those without a familar hisitory. In contrast, such differences did not exist in the children with periodontal risk, whether or not they had a family history of hyperlipidaemia. Co-occurrence networks showed that these differences in children with no periodontists risk were linked to the presence of fewer oral microbial networks, but more microbes linked to mature plaque structures. In contrast, children with periodontal risk markers, regardless of family history of hyperlipidaemia, contained co-occurrence networks that were associated with microbes linked to periodontal disease. Conclusions In children diagnosed with T1D, our findings support an association between oral microbiota and two different exposure variables: familial history of hyperlipidaemia and periodontal risk factors.